Genetic Diversity of Mycolactone Producing Mycobacteria Causing Buruli Ulcer in Ghana and Côte D’ivoire - Dogbe, M. (University of Ghana, 2019)
Buruli ulcer remains a neglected tropical disease endemic in Africa especially Ghana and Côte d’Ivoire. It is a necrotizing skin and soft tissue infection caused by Mycobacterium ulcerans which produces mycolactone which causes adverse effects associated with disease in humans. Other mycolactone producing bacteria (MPMs) have been identified to cause granulomas in fish and frog. There are limited advanced genetic tools for studying transmission of the diseases and for carrying out molecular epidemiological studies. The mycolactone producing mycobacteria (MPM), M. shinshuense has been reported to cause Buruli ulcer and other studies have revealed several MPM infections other than M. ulcerans in clinical samples. It is therefore imperative to know the exact MPMs that are in circulation by genotypically distinguishing them using molecular tools. Patients with Buruli ulcer-like disease presentation were recruited from endemic communities in Ghana and Côte d’Ivoire. Swabs and FNA samples were screened using primers detecting the insertion sequence 2404 gene and the Enoyl reductase gene. Genotyping was achieved at 16 MU VNTR loci and length polymorphisms arising from differences in tandem repeats for samples were validated using six (6) controls and sequencing. A total one hundred and fifty-nine (159) of the 189 samples were confirmed as Buruli ulcer positive. Genotyping was successful for all controls (100%) and most samples (69%) at all sixteen (16) VNTR loci. Seven (7) MU genotypes designated, A, B, C, D, E, F and G and five MPM genotypes MLF (Mycobacterium liflandii), MHB (Mycobacterium marinum hybrid), MDL (Mycobacterium marinum DL), MCL (Mycobacterium marinum CL) and MSA (Mycobacterium marinum SA) were generated samples were assigned genotypes based on their VNTR profiles. Genotypes C, D and F were present in both Ghana and Côte d’Ivoire. However, genotypes E and MLF were only found in Ghana whiles Genotype A and G were found in only Côte d’Ivoire Genotype D has persisted over the years from 2008 to 2019 comparing this study to published data. These findings support the hypothesis that Mycolactone producing mycobacteria causing Buruli ulcer in Ghana and Côte d’Ivoire are diverse and affirms VNTR typing as a comparably useful tool for differentiating MU strains as well as other MPMs in Buruli ulcer endemic communities.
MPhil. Mol. Cell Biology of Inf. Diseases
Keywords: Mycolactone; Mycobacteria; Buruli Ulcer; Ghana; Côte D’ivoire